Assessment of different inert dust formulations for the control of Sitophilus oryzae, Tribolium confusum and Aphis fabae. (November 2020) - Faliagka, Sofia; Agrafioti, Paraskevi; Lampiri, Evagelia; Katsoulas, Nikolaos; Athanassiou, Christos G.
Abstract: The necessity to ensure the quality of food by simultaneously reducing the environmental footprint due to the extensive use of convectional insecticides has led to an increase in the efforts towards the development of non-chemical control strategies. Silicon dioxide is considered as a promising alternative active ingredient for the control of various arthropods in different crops and products. Silicon dioxide and the relative silicaceous materials (silica) are classified in the category of inert dusts, which act on arthropods through contact leading to desiccation. In our study, we tested three different silica-based dust formulations, Sylobloc® S200, Syloid® ED3 and Syloid® ED5 in order to evaluate their pest control efficacy. As target species, we used, in laboratory bioassays, a field/greenhouse pest the aphid Aphis fabae and the stored-product pests Tribolium confusum and Sitophilus oryzae . These species were exposed to the aforementioned dusts under three different doses (0, 12.5, 25.0 mg/petri) and different time intervals. Taking into account the exposure time of the above species to the inert dusts, S. oryzae adults and T. confusum larvae were more susceptible to ED5 at 25.0 and 12.5 mg, respectively, while A. fabae adults to S200 at the highest tested dose, since less time was needed in order to achieve the highest mortality. Sitophilus oryzae and T. confusum mortality was increased to 90% after the 7th day of post exposure period to all dust formulations, while the highest mortality levels of A. fabae were recorded after 1 day of post exposure to S200. The results of this study show that these silicon dust formulations are effective to greenhouse and storage insect control and can be further exploited through various uses, e.g. in insect-proof nets to minimize the pest invasions in greenhouses. Highlights: Silicon dust formulations (S200, ED3, ED5) are effective to greenhouse and storage insect control. Sitophilus oryzae adults and Tribolium confusum larvae were more susceptible to ED5 at 25.0 and 12.5 mg/petri, respectively. Aphis fabae adults were more susceptible to S200 at 25.0 mg/petri. After 7 d of post exposure period, 90% mortality was recorded in S. oryzae and T. confusum in all formulations. The highest mortality levels of A. fabae were recorded after 1 d of post exposure to S200.